PENGENALAN PENGOLAHAN SAMPAH UNTUK ANAK-ANAK TAMAN KANAK-KANAK MELALUI MEDIA BANNER - Pratiwi, Dasrieny (Bioedukasi Jurnal Pendidikan Biologi, 2016)
Everybody have a responsibility for their enviroment to kept clean. Human population as a important part of environment problems.  All activity that human do will produce the rubbish, and it makes big persentage to contribute to make enveroment will be dirty in this world.  Because everybody will produce about 1 Kg for day and, a half ton every years.  Bad management it makes negative effect for human healty.  And good management will be good solution for enveroment problems, as spacial rubbish.  Introducting rubbish management to children under five years its mean to solve a problems for logtherm.  Basicly kindergarthen cant read well.  So that, the way to introducting use a banner media. By this way, a little word an many picture will make they understand abbout the message for manage the rubbish.   When this way were appicated in five school, not only student was interset to this media (banner) but, a parents who attend their also enthusiast to following this activity.  Kata kunci:Pengenalan pengelolahan sampah, media banner.